Aluminum and Amyloid-β in Familial Alzheimer’s Disease - Mold, Matthew; Linhart, Caroline; Gómez-Ramírez, Johana; Villegas-Lanau, Andrés; Exley, Christopher (Journal of Alzheimer's disease, 2020)
Genetic predispositions associated with metabolism of the amyloid-β protein precursor underlie familial Alzheimer’s disease; a form of dementia characterized by early disease onset and elevated levels of cortical amyloid-β. Human exposure to aluminum is linked to the etiology of Alzheimer’s disease and recent research measured a high content of aluminum in brain tissue in familial Alzheimer’s disease. To elaborate upon this finding, we have obtained brain tissues from a Colombian cohort of donors with familial Alzheimer’s disease. We have used established methods to measure the aluminum content of these tissues and we have compared the data with a recently measured dataset for control brain tissues. We report significantly higher levels of aluminum in brain tissues in donors with familial Alzheimer’s disease than in control tissues from donors without neurological impairment or neurodegeneration. We have used aluminum-specific fluorescence microscopy along with complementary imaging for amyloid-β to demonstrate a very high degree of co-localization of these two risk factors in brain tissue in familial Alzheimer’s disease. Aluminum and amyloid-β were co-located in senile plaques as well as vasculature, the latter resembling cerebral amyloid angiopathy. Aluminum was also found separately from amyloid-β in intracellular compartments including glia and neuronal axons. The research has identified an arguably unique association between high brain aluminum content and amyloid-β and allows postulation that genetic predispositions defining familial Alzheimer’s disease underlie this relationship.